Implementasi ReactJS dan Firebase untuk Pengembangan Aplikasi Perencanaan Keuangan Pegawai di Nurul Fikri Academy - Nelan Nelan; Nasrul Nasrul; Reza Maulana (LPPM STT Terpadu Nurul Fikri, 2026)
Effective financial planning is an important aspect in supporting employee welfare. Within Nurul Fikri Academy, there is no integrated digital system that enables employees to conduct financial planning independently. This research aims to develop a web-based financial planning application designed to record, monitor, and analyze employee financial conditions. The application is built using the ReactJS framework for an interactive user interface and Firebase as the backend, providing authentication and real-time data storage. The development method used is Extreme Programming (XP), through the stages of planning, designing, coding, and testing. The main features of the application include financial calculators (emergency funds, pensions, and investments), user discussion forums, and financial education articles. Testing was conducted using Blackbox Testing and User Acceptance Testing (UAT) methods. The test results show that all features run well across various devices, with a UAT success rate of 90%, exceeding the minimum threshold of 80%. This application is expected to be an effective solution for improving employees' literacy and financial management skills in a structured, efficient manner.